Retrospective insights into probiotic and prebiotic interventions: associations with gut microbiota profiles and nutritional outcomes - He, Xueli; Chen, Chaoming; Shen, Lan; Su, Xiaomei; Xie, Hao; Yang, Mengsi; Jiang, Wenkang (Frontiers in Nutrition, 2026)
BackgroundProbiotics and prebiotics are known to regulate the gut microbiota, however, their relations with the metabolic and nutritional outcomes in adults are under-investigated in practical environments.ObjectiveTo provide light on microbiome-targeted metabolic health initiatives, this retrospective study investigates relationships among probiotic and prebiotic therapies, gut microbiota profiles, and nutritional outcomes.MethodsClinical and nutritional history (n = 350 adults) in probiotic (n = 140), prebiotic (n = 120), and control (n = 90) were compared. The microbiota data were obtained with the help of 16S rRNA sequencing in the stool samples at baseline and 4–12 weeks of the intervention. Alpha (Shannon, Simpson) and beta diversity (Bray-Curtis) was evaluated by means of PERMANOVA, and the relative abundance of the main taxa (Lactobacillus spp., Bifidobacterium spp., Faecalibacterium prausnitzii) was determined. The adjusted ANCOVA and multivariate regression models adjusted to the difference between baseline were used to analyze the anthropometric and biochemical outcomes, including body mass index (BMI) and lipid profiles.ResultsAlpha diversity (Shannon index: probiotics 3.4–4.2, p < 0.01; prebiotics 3.3–4.0, p < 0.01) and beta diversity clustering (PERMANOVA R2 = 0.12, p < 0.001 in probiotics) were significantly increased by the use of probiotics and prebiotics, respectively. Lactobacillus (2.1–4.8%, p < 0.01) and Bifidobacterium (3.5–7.9%, p < 0.001) were increased due to probiotic supplementation, whereas Bifidobacterium (3.7–6.8%, p < 0.001) and F. prausnitzii (6.1–8.3%, p = 0.04) were increased due to prebiotics supplementation. The two interventions were better than controls in terms of BMI and lipid levels (reduction of BMI: probiotics −1.6 + − 0.4 kg/m2, prebiotics −2.0 + − 0.5 kg/m2; total cholesterol: probiotics −18 + −5 mg/dL, prebiotics −17 + −6 mg/dL; all p < 0.05).ConclusionThe use of probiotic and prebiotic supplementation was found to be related to an augmented gut microbial and better metabolic results in grown-ups. Such results point to possible advantages of the dietary microbiota modulation, but due to the retrospective design, it is not possible to make causal conclusions.